The Tourist Experience / A New Introduction - Ryan Chris (Cassell, 1998)
This study of the Tourist experience draws on a wealth of data from tourists world-wide and from the work of researchers. Preface, Acknowledgements, The Chase of a Dream and the End of a Play, Similar Motivations and Diverse Behaviors, From Motivation to Assessment, Vital Encounters: When Tourists Contact Travel Agents, Making or breaking the Tourist Experience: The Role of Human Resource Management, Urban Tourism: Analyzing and Evaluating the Tourist Experience, Special Event Motivations and Behavior, Memories of the Beach, Heritage Tourism under Post-Modernity: Truth and the Past, ''The Time of Our Lives'' or Time for Our Lives: An Examination of Time Holidaying, References, Name and Subject Index.